2010
DOI: 10.1161/circulationaha.109.928085
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Clinical and Hemodynamic Performance of the Hancock II Versus the Perimount Aortic Bioprostheses

Abstract: Background-The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
38
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 24 publications
3
38
2
Order By: Relevance
“…The preoperative demographics of patients in this study cohort were similar to other studies describing outcomes following AVR or MVR. [2][3][4][5][6][7][8] In the present study, younger patients who underwent bioprosthetic AVR were less likely to be female, have preoperative atrial fibrillation, and undergo concomitant CABG. Younger patients who underwent MVR were also less likely to require concomitant CABG.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…The preoperative demographics of patients in this study cohort were similar to other studies describing outcomes following AVR or MVR. [2][3][4][5][6][7][8] In the present study, younger patients who underwent bioprosthetic AVR were less likely to be female, have preoperative atrial fibrillation, and undergo concomitant CABG. Younger patients who underwent MVR were also less likely to require concomitant CABG.…”
Section: Discussionmentioning
confidence: 53%
“…1 Large cohort studies have indicated that excellent survival and freedom from valve-related complications, including reoperation, are associated with the use of a bioprosthesis for left heart valve replacement in patients older than 65 years. [2][3][4][5][6][7][8] Younger patients also may opt for a bioprosthesis at the time of valve surgery to avoid long-term oral anticoagulation, which is associated with hemorrhage and worse disease perception. 9 Recent North American data indicate that bioprostheses are increasingly used in patients less than 65 years of age who undergo aortic valve replacement (AVR) or mitral valve replacement (MVR).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Good long-term results of bioprosthesis implantation in older patients are well known [1315]. Long-term results of implantation of currently available bioprostheses are comparable [16, 17]. Very good results of bioprosthesis implantation in patients who underwent surgery under the age of 60 years and were followed for over 20 years were presented by Ruel et al [18].…”
Section: Discussionmentioning
confidence: 99%
“…23,48,72,74 The second generation of heart valves treated by zero to low pressure fixation (e.g., the Hancock II porcine valve, Medtronic, Inc, Minneapolis, MN, and the Carpentier-Edwards Perimount TM , Edwards Lifesciences, Irvine, CA), have been implanted in patients for more than two decades with minimal problem. 27,36,109 Alternatively, third generation of heart valves such as Carpentier-Edwards Magna model of the Perimount TM pericardial prosthesis (Edwards Lifesciences, Irvine, CA) and the Mosaic porcine valve (Medtronic, Inc., Minneapolis, MN) have only been implanted for approximately 13 years. 34,73,133,134 , making it too early to determine their durability compared to older generations.…”
Section: Accelerated Wear Testingmentioning
confidence: 99%